PROBABILISTIC-PHYSICAL APPROACH TO DESCRIBE AND DETERMINE THE RELIABILITY OF CARS - Muradian, L. A. (Science and Transport Progress, 2016)
Purpose. The article aims to develop an algorithm and a sequence of description and determination of car reliability to predict certain quantitative indicators of the studied elements, parts and units, or a car as a whole on the basis of probabilistic-physical approach. Methodology. For the calculation of the indicators of reliability, durability and safety of cars the probabilistic-physical method was used, which takes into account the resources consumption inevitable in the operation of cars. The methodology of quantifying the reliability is based on the study of the physical-mechanical and physical-chemical properties and parameters of various elements, with the identification of principles of the aging processes of the elements or parts (with operating time) to determine the analytical dependencies of these processes from the indicators of cars reliability. Findings. On the basis of probabilistic-physical approach it was developed a model to describe and determine the reliability of the cars. At this the method of calculation based on probabilistic-physical model is fundamentally different from all known rigorous probabilistic methods by the fact that it considers a continuous set of states of the elements, parts and systems of the car during continuous time. If there exists or (if it possible to find) the information parameter about the resource consumption of the car element with evaluation of its change speed, and knowing its limit, based on the built car reliability model with the involvement of probabilistic-physical approach, one can predict all the necessary quantitative indicators of reliability of the studied elements, parts and units or a car as a whole. Originality. The methodology of the reliability construction with the use of probabilistic-physical model with DN-distribution was further developed in the article. The specific physical interpretation of the constants of DN-distribution of failures makes it possible to evaluate them according to the results of the study of certain parameters characterizing the technical condition of the car. On the basis of probabilistic-physical approach the algorithm and the sequence of description and determination of cars reliability to predict certain quantitative reliability indicators of the studied elements, parts and units, or a car as a whole were developed. Practical value. The results make it possible to calculate in practice the quantitative indicators of reliability of cars or their individual elements for further prediction of the overall reliability during operation.